Efektivitas Program Bimwin di KUA: Tinjauan Manajemen Pendidikan atas Kepdirjen 172/2022: The Effectiveness of Bimwin at KUA: An Educational Management Analysis of the Implementation of the Decree of the Director General of Islamic Community Guidance No. 172 of 2022 - Mesraini; Suwendi; Mohamad Abror (Direktorat Jenderal Bimbingan Masyarakat Islam, 2026)
This article examines the gap between the implementation standards for Marriage Guidance (Bimbingan Perkawinan, Bimwin) established in Decree of the Director General of Islamic Community Guidance No. 172 of 2022 and the effectiveness of implementation at Offices of Religious Affairs (Kantor Urusan Agama, KUA). It aims to explain Bimwin as an adult-education program and to assess how regulatory provisions interact with managerial capacity through planning, organizing, leadership, and supervision. The study uses a descriptive qualitative approach and document analysis of the 2022 decree and 23 accredited scholarly journal articles published between 2021 and 2025. The documents were analyzed by inventorying regulatory provisions, coding evidence according to the four management functions, comparing policy standards with recurring implementation patterns, and conducting a cross-source synthesis. The findings show that the decree provides an operational framework covering participant eligibility, three delivery modes, instructional duration and sessions, organizers, facilitators, financing, and administrative reporting. Substantive effectiveness, however, remains uneven. In planning, national standards are not consistently translated into needs assessment and measurable learning outcomes. In organizing, facilitator availability, budgets, partnerships, and facilities vary among KUA. In leadership, learning quality depends on facilitators’ capacity to apply adult-oriented, dialogical, and contextual methods. In supervision, reporting remains more effective at documenting program delivery than at measuring changes in participants’ knowledge, attitudes, and marital readiness. The article’s novelty is an integrated learning-governance model in which the four functions mediate the relationship between regulation and Bimwin outcomes. The practical implication is that KUA should institutionalize needs assessment, facilitator competency standards, cross-sector coordination, pre- and post-assessment, and proportionate follow-up so that administrative compliance develops into educational effectiveness and stronger family resilience.